Human resources management : concepts, methodologies, tools and applications (Business Science Reference, 2012)
"This reference compiles the most sought after case studies, architectures, frameworks, methodologies, and research related human resources management, Including in-depth analyses on the fundamental aspects, tools and technologies, methods and design, applications, managerial impact, social/behavioral perspectives, critical issues, and emerging trends in the field"--Provided by publisher.